Model Antecedents of Halal Tourism: A Review - Erwan Iskandar; Eman Sulaiman (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — The purpose of this study was to examine the antecedents of halal tourism and their implications for destination development and marketing. Research method— The research method employed was a systematic literature review, which involved searching and analyzing relevant scholarly articles and publications.Result— The results of the study revealed several key findings. Destination attributes, including halal-friendly facilities and services, emerged as crucial factors in attracting Muslim travelers. Effective marketing and promotion strategies, infrastructure and services, cultural and religious considerations, and socio-economic factors were also identified as significant determinants of halal tourism. These findings contribute to a better understanding of the factors that shape the growth and success of halal tourismConclusion— The antecedents of halal tourism play a vital role in attracting and satisfying the needs of Muslim travelers. Destinations and tourism stakeholders should consider these factors in their planning, development, and marketing efforts to tap into the growing halal tourism market. The practical implications of this study suggest that investing in halal-friendly facilities, implementing targeted marketing strategies, and respecting cultural and religious practices can enhance the competitiveness and sustainability of destinations in the halal tourism industry.